The Effects of Amlodipine on the Biochemical and Histopathological Changes in the Rabbit Ileum Subjected to Ischemia-Reperfusion - A. Kagan Coskun; Armagan Gunal; Zekai Halici; Akgun Oral; Melik Seyrek; Yasin Bayir; Cenk Kilic; Taner Yigit; Tahir Ozer; A. Ihsan Uzar (Eurasian Journal of Medicine, 2011)
Objective: The aim of this study was to determine the potential, protective effects of amlodipine in an experimental, ischemia-reperfusion (I/R) model in the rabbit small intestine. Materials and Methods: The rabbits were divided into four groups: sham-operated, amlodipine (10 mg/kg) + sham-operated, I/R, and I/R + amlodipine (10 mg/kg) groups. An intestinal I/R model was applied to the rabbits. The superior mesenteric artery was occluded for 1 h with an atraumatic vascular clamp and then was reperfused for 2 h. Animals in the amlodipine and I/R + amlodipine groups received the amlodipine by oral gavage. At the end of the 2-h-reperfusion period, the animals were sacrificed. Results: Pretreatment with amlodipine significantly increased SOD activity and GSH levels to values close to those found in the serum from the I/R group. Rabbits in the I/R group showed high levels of serum MDA. Amlodipine pretreatment significantly reduced the serum MDA levels compared to the I/R group, although the MDA levels in the I/R + amlodipine group were still higher than in the sham-operated group. The I/R damage was ameliorated by amlodipine pretreatment, as evidenced by histopathological analysis. Conclusion: The present study is the first to report an attenuation of I/R-induced intestinal injury by the systemic administration of amlodipine.